Miejsce Stolicy Apostolskiej w polskiej polityce zagranicznej w latach 1989-1993 - Krzysztof Skubiszewski (Ksiegarnia Akademicka Publishing, 2014)
The article discusses the principles of the Polish foreign policy and tries to identify the shared principles with the diplomacy of the Holy See. Author concentrates on the three major issues. The first one is devoted to the recognition of the role of morality in international relations which should be clearly distinguished from being confused with any ideology. The second one deals with the human rights and basic liberties in the light of the results of the Second Vatican Council which identified the notion of human dignity as their basis. The third one shared principle is the strong support for the idea of European integration and unity.